Theoretical concepts in physics : an alternative view of theoretical reasoning in physics - Longair, Malcolm 1941- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"In this original and integrated approach to theoretical reasoning in physics, Malcolm Longair illuminates the subject from the perspective of real physics as practised by research scientists. Concentrating on the basic insights, attitudes and techniques that are the tools of the modern physicist, this approach conveys the intellectual excitement and beauty of the subject"--
Includes bibliographical references and indexes.
Keywords: Mathematical physics